Fuel cell powered octocopter for inspection of mobile cranes: Design, cost analysis and environmental impacts. (1st April 2018) - Belmonte, N.; Staulo, S.; Fiorot, S.; Luetto, C.; Rizzi, P.; Baricco, M.
Highlights: Design and sizing of two propulsion systems for mini UAV. Comparison of two propulsion systems: fuel cell and lithium-ion battery. Cost analysis show that power system based on hydrogen technology is more expensive. LCA shows low environmental impacts for both fuel cell and battery. Abstract: In this paper, the possible development of a drone for mobile crane inspection is investigated. Since the flying time of the drones currently in commerce is too short for the designed application, proton exchange membrane fuel cells and lithium-ion batteries are considered as alternative power systems to extend the flying time. Both systems are analyzed from an economical point of view and a life cycle assessment is performed to identify the main contributors to the environmental impact. From a commercial point of view, the lightweight fuel cell, being a niche product, results more expensive with respect to the Li-ion battery. On the other hand, the life cycle assessment results show a lower burdens of both technologies with respect to other components of the two systems, as carbon fiber. The source of the hydrogen and the electricity mix play a critical role as well.